2024
DOI: 10.1038/s41467-023-44520-4
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid beta 42 alters cardiac metabolism and impairs cardiac function in male mice with obesity

Liam G. Hall,
Juliane K. Czeczor,
Timothy Connor
et al.

Abstract: There are epidemiological associations between obesity and type 2 diabetes, cardiovascular disease and Alzheimer’s disease. The role of amyloid beta 42 (Aβ42) in these diverse chronic diseases is obscure. Here we show that adipose tissue releases Aβ42, which is increased from adipose tissue of male mice with obesity and is associated with higher plasma Aβ42. Increasing circulating Aβ42 levels in male mice without obesity has no effect on systemic glucose homeostasis but has obesity-like effects on the heart, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“… 191 , 203 Interestingly, adipose tissue expresses and releases Aβ42 into circulation. 204 Some obesity‐related brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia‐relevant brain regions such as the hippocampus. 205 Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction.…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%
“… 191 , 203 Interestingly, adipose tissue expresses and releases Aβ42 into circulation. 204 Some obesity‐related brain changes may be caused by dysregulation of adipokines such as leptin, which are secreted by adipose tissue and can influence plasticity, neurogenesis and inflammatory cytokine production in dementia‐relevant brain regions such as the hippocampus. 205 Studies in AD models have suggested that leptin may have a therapeutic role in reducing Aβ and intracellular tau phosphorylation, thereby preventing synaptic dysfunction.…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%